Penggunaan Media Kolase Untuk Meningkatkan Kemampuan Gerak Motorik Halus Siswa Tunagrahita Ringan di SDLB Negeri Banda Aceh - Aida Fitri; Syaiful Bahri; Fajriani Fajriani (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
ABSTRACTOn students ' mental retardation, fine motor ability is indispensable in conducting daily activities that require them to learn more independently and not continue to depend on other people. This research aims to improve the ability of students ' fine motor motion light mental retardation in SDLB Land Banda Aceh through the use of Media collage. Collage is a technique of sticking to a range of elements into a frame so that it generates a new artwork, materials affixed like material such as paper, cloth, grain, dry leaves and so on. This type of research method using research case studies (case study), with a mixed method (mixed methods), which is a method that combines quantitative and qualitative approaches. The subject taken with purposive sampling methods that add up to 2 people. Data collection is done using an instrument of observation through the test Act and the use of the interview. Implementation of the research carried out for 14 times, with a time of 45 minutes/session. The research scoring results retrieved changes i.e. score post-test score higher than pre-test. As well as the results of the analysis of the qualitative data indicates the motion of fine motor ability of the students of mild mental retardation increased from undeveloped stage (BB) to the stage of developing appropriate expectations (BSH), started to grow (MB) to the very well developed (BSH).